2021
DOI: 10.1097/mcc.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive respiratory support for acute respiratory failure due to COVID-19

Abstract: Purpose of review Noninvasive respiratory support has been widely applied during the COVID-19 pandemic. We provide a narrative review on the benefits and possible harms of noninvasive respiratory support for COVID-19 respiratory failure. Recent findings Maintenance of spontaneous breathing by means of noninvasive respiratory support in hypoxemic patients with vigorous spontaneous effort carries the risk of patient self-induced lung injury: the benefit of averting intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 132 publications
2
19
0
4
Order By: Relevance
“…Despite the good outcomes of NIV in COVID-19, delayed detection of its failure carries serious hazards, such as patient-induced lung injury due to exaggerated swings in the pleural pressure due to high inspiratory efforts, alveolar flooding, and pulmonary oedema due to increased transmural pressure in lung vessels, unplanned emergency intubation which is life-threatening to the patient [2] , and carries the risk of disease transmission to healthcare providers. Therefore, it is essential to have easy and accurate monitoring tools to determine the optimal timing of invasive ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the good outcomes of NIV in COVID-19, delayed detection of its failure carries serious hazards, such as patient-induced lung injury due to exaggerated swings in the pleural pressure due to high inspiratory efforts, alveolar flooding, and pulmonary oedema due to increased transmural pressure in lung vessels, unplanned emergency intubation which is life-threatening to the patient [2] , and carries the risk of disease transmission to healthcare providers. Therefore, it is essential to have easy and accurate monitoring tools to determine the optimal timing of invasive ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…There is wide agreement on the use of non-invasive ventilation (NIV) to manage patients with COVID-19 [1] . However, NIV failure, if not detected early, carries several hazards such as patient self-induced lung injury and unplanned intubation [2] .…”
mentioning
confidence: 99%
“…[ 6 ] With the COVID-19 pandemic, its application in patients with hypoxemic respiratory failure has become increasingly common. [ 92 ] Traditionally, CPAP is administered through a high-flow generator (turbines, Venturi systems, or air/oxygen blenders) delivering fresh gas flow in an inlet port, and an adjustable PEEP valve connected to an outlet port. Its simplicity makes CPAP highly cost-effective in the emergency context and easily used outside of intensive care since ventilators are not strictly necessary.…”
Section: Nivmentioning
confidence: 99%
“…CPAP was widely used at the outset of COVID-19, with conflicting results. [ 92 , 98 ] Recently, a large adaptive, parallel group randomized clinical trial showed reduced intubation rates in patients treated with CPAP compared with a standard oxygen therapy group. [ 99 ] Furthermore, Perkins et al.…”
Section: Nivmentioning
confidence: 99%
“…28 Moreover, the saturation of high-dependency units and ICUs has often forced the use of NIV also in patients with moderate-to-severe hypoxemia, with the application of high airway pressures and/or high FiO 2 and for prolonged periods of time. 29…”
Section: Rationalementioning
confidence: 99%